2010
DOI: 10.3233/br-2010-004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the health benefits of fruits for physical fitness: A research platform

Abstract: To evaluate the health promoting attributes of fruits and their compounds the New Zealand Institute for Plant & Food Research Ltd (PFR) is using exercise as a model for oxidative stress and immune depression. Regular exercise has health benefits believed to be derived from adaptive responses to moderate oxidative stress. However, following exhaustive or unaccustomed exercise, excessive and prolonged oxidative stress and inflammation can be detrimental and the right balance of modulation from nutritional suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…An alternative explanation to regional or seasonal factors in these marked variations might be differences in analytical methods or extraction protocols. In choosing literature data, we selected only those reports which used similar methods to ours [30], i.e., solvent extraction of fresh fruit, followed by HPLC measurements, calibrated using authentic standards. Some reports involved extraction of dried fruit and are therefore not comparable.…”
Section: Comparison With New Zealand Content Datamentioning
confidence: 99%
“…An alternative explanation to regional or seasonal factors in these marked variations might be differences in analytical methods or extraction protocols. In choosing literature data, we selected only those reports which used similar methods to ours [30], i.e., solvent extraction of fresh fruit, followed by HPLC measurements, calibrated using authentic standards. Some reports involved extraction of dried fruit and are therefore not comparable.…”
Section: Comparison With New Zealand Content Datamentioning
confidence: 99%
“…Strawberry fruits are regarded as having considerable health benefits, primarily because of the antioxidant content, which can protect the human body against cellular oxidation reactions (Seeram 2008, Henning et al 2010, Schrage et al 2010. Genetic background significantly influences the agronomic characteristics, fruit quality and phytochemical activity of strawberries.…”
Section: Effect Of Genotypesmentioning
confidence: 99%
“…The cultivar with the greatest concentration of cyanidin 3‐ O ‐glucoside (C3G) was Ben Ard (314 µg/mL) and for cyanidin 3‐ O ‐rutinoside (C3R) it was L700 (3,138 µg/mL; Parkar et al., ). Other research on the ANC content of New Zealand BC cultivars compared with Non‐New Zealand cultivars arrived at a similar conclusion and determined that New Zealand BC cultivars possess approximately 1.5 times more ANC (Schrage et al., ). Total ANC from 107 genotypes of Vaccinium L ., Rubus L ., and Ribes L .…”
Section: Chemistry and Sensory Properties Of Bcmentioning
confidence: 72%
“…Both animal and human studies reported the effects of BC and BCE on athletic training and performance. It was demonstrated that BC and BCE reduce oxidative stress-related injuries that cause fatigue and damage (Braakhuis, Hopkins, & Lowe, 2014;Hurst, 2015;Hurst & Hurst, 2013;Schrage et al, 2010). It has also been well documented that flavonoids protect retinal cell types from death due to oxidative stress (Kalt, Hanneken, Milbury, & Tremblay, 2010).…”
Section: Health Benefits Of Bioactive Compounds From Bcmentioning
confidence: 99%